2016
DOI: 10.1063/1.4954376
|View full text |Cite
|
Sign up to set email alerts
|

The kinetic origin of delayed yielding in metallic glasses

Abstract: Recent experiments showed that irreversible structural change or plasticity could occur in metallic glasses (MGs) even within the apparent elastic limit after a sufficiently long waiting time. To explain this phenomenon, a stochastic shear transformation model is developed based on a unified rate theory to predict delayed yielding in MGs, which is validated afterwards through extensive atomistic simulations carried out on different MGs. On a fundamental level, an analytic framework is established in this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Apart from this, quenching is also used to freeze in (vitrify) the high temperature structure at low temperatures. The best-known examples for those are metallic glasses 1 , 2 and high entropy alloys 3 formed at 10 6 to 10 12 °C s −1 cooling rates 4 . Phase selection using controlled cooling rates in these materials is crucial to arrest (select) structures that translate into desirable macroscopic properties for various engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, quenching is also used to freeze in (vitrify) the high temperature structure at low temperatures. The best-known examples for those are metallic glasses 1 , 2 and high entropy alloys 3 formed at 10 6 to 10 12 °C s −1 cooling rates 4 . Phase selection using controlled cooling rates in these materials is crucial to arrest (select) structures that translate into desirable macroscopic properties for various engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study on the yielding of MGs by Ye et al . 32 also showed that shear bands could form within the elastic stress range if a sufficient waiting time is provided. Hence the cycling frequency is expected to affect the shear banding behavior.…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, the ST events can be preferentially activated at the weakest configurations due to their low shear modulus. In a metallic glass specimen experiencing a uniaxial stress lower than the yield strength, the solute-centered clusters and the superclusters act as the elastic backbone, while the scattered ST events activated at the weakest configurations contribute to the inelastic part [59]. As long as the isolated ST events do not percolate to a sizable length-scale, they can be reversed with the aid of the back-stress from the backbone upon unloading and the metallic glass behaves elastically on the macroscopic scale [60,61].…”
Section: Discussionmentioning
confidence: 99%